Hybrid glass optical fibers-novel fiber materials for optoelectronic application - Shiliang Kang; Guoping Dong; Jianrong Qiu; Zhongmin Yang (Optical Materials: X, 2020)
Hybrid glass optical fibers incorporated with optoelectronic materials and functionalities are highly anticipated for potential applications in optical communication, remote sensing, biomedicine, and nonlinear optics. However, the design and construction of hybrid glass fibers present significant challenges due to restrictions on the composition of fiber fabricated using conventional chemical vapor deposition (CVD) methods and the difficulty in maintaining the optoelectronic performance stably of fiber prepared by common rod-in-tube fiber-drawing technique. In this review, a versatile fiber-drawing approach which is called “melt-in-tube” (MIT) or “molten core” is presented to produce hybrid glass optical fibers. During the fiber-drawing process, the core is melted whereas the cladding is only just softened. The recent advances of the hybrid glass fibers including glass core-glass cladding fiber, crystal core-glass cladding fiber, and semiconductor core-glass cladding fiber are reported. In addition, the extensive applications of the hybrid glass fibers in the fields of fiber laser, fiber sensing, frequency conversion, photodetection and thermoelectric conversion are also discussed. These breakthroughs and advances in novel fiber materials and applications offer new opportunities for the research and development of optoelectronic devices.